Electron Scattering in Gases - from Cross Sections to Plasma Modeling - Karwasz, Grzegorz Piotr (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The first experiments on electron scattering were completed before the "official" discovery of this particle by J. J. Thomson. In spite of this, our knowledge of cross sections is still far from complete.More recent experiments had some unexpected results, like selective fragmentation of DNA constituents by low-energy electrons, or "reverse" phenomena, i.e., synthesis of simple amino acids from inorganic precursors, triggered by slow electrons. The most recent need for cross sections comes from modeling plasmas for industrial and thermonuclear applications, and atmospheres of solar and extra-solar planets.Both fundamental research (experiments, theory, reviews) and applications of electron-scattering cross sections in various processes are welcome.